3.6(j+4)=1.4(16+j)

Simple and best practice solution for 3.6(j+4)=1.4(16+j) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.6(j+4)=1.4(16+j) equation:


Simplifying
3.6(j + 4) = 1.4(16 + j)

Reorder the terms:
3.6(4 + j) = 1.4(16 + j)
(4 * 3.6 + j * 3.6) = 1.4(16 + j)
(14.4 + 3.6j) = 1.4(16 + j)
14.4 + 3.6j = (16 * 1.4 + j * 1.4)
14.4 + 3.6j = (22.4 + 1.4j)

Solving
14.4 + 3.6j = 22.4 + 1.4j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-1.4j' to each side of the equation.
14.4 + 3.6j + -1.4j = 22.4 + 1.4j + -1.4j

Combine like terms: 3.6j + -1.4j = 2.2j
14.4 + 2.2j = 22.4 + 1.4j + -1.4j

Combine like terms: 1.4j + -1.4j = 0.0
14.4 + 2.2j = 22.4 + 0.0
14.4 + 2.2j = 22.4

Add '-14.4' to each side of the equation.
14.4 + -14.4 + 2.2j = 22.4 + -14.4

Combine like terms: 14.4 + -14.4 = 0.0
0.0 + 2.2j = 22.4 + -14.4
2.2j = 22.4 + -14.4

Combine like terms: 22.4 + -14.4 = 8
2.2j = 8

Divide each side by '2.2'.
j = 3.636363636

Simplifying
j = 3.636363636

See similar equations:

| 6-5[4-(6y-3)]= | | 3x^5y^3/10x^3x20x/12y^4 | | 4=-2(x)(x)+3 | | 10a+8(a-3)=15 | | 4=-2x+3 | | 2x+40-4x=1-7x+4 | | 1205(2w-13)=3(2w-5) | | 2ab*3+3xb*2-5b*4+2b*2= | | csquared-5c=0 | | 5n+6n^4-7n+15n^4+13n=x | | (5x-8)(x^2+9x-10)= | | 3x^4+12x^3-36x^2=0 | | 1.4-0.2x=3.2 | | 0.07+0.4x=2 | | 5n-1=2n+8 | | 3b-9-86=11 | | -3p+2=2p+12 | | 3x^1+12x=0 | | 8lx-9l+8=32 | | 4m+7=9m-3 | | 2.4=4.2 | | 1008/48 | | 3(9-8x)+8(3x+4)=11 | | 5x-2y+20=0 | | 10-(4x-5)=6-5x | | 4w-16=12+3w | | 5w-2(w-18)=7w-15 | | (x+1)/(x-3)-3/5=4/(x-3) | | 2d^2+12d/d+6 | | 4x+5=3(x+15) | | x(3x-2)+x(4x-5)=(7x+4)(x-1) | | x+1/x-3-3/5=4/x-3 |

Equations solver categories